2008
DOI: 10.1370/afm.762
|View full text |Cite
|
Sign up to set email alerts
|

Data Collection Outcomes Comparing Paper Forms With PDA Forms in an Office-Based Patient Survey

Abstract: PURPOSEWe compared the completeness of data collection using paper forms and using electronic forms loaded on handheld computers in an offi ce-based patient interview survey conducted within the American Academy of Family Physicians National Research Network. METHODSWe asked 19 medical assistants and nurses in family practices to administer a survey about pneumococcal immunizations to 60 older adults each, 30 using paper forms and 30 using electronic forms on handheld computers. By random assignment, the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 11 publications
4
50
0
Order By: Relevance
“…A randomized trial by Galliher and colleagues 7 compares the use of handheld computers with paper forms for data collection in a national practice-based research network. They fi nd interesting tradeoffs between the 2 data collection methods.…”
Section: Revealing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized trial by Galliher and colleagues 7 compares the use of handheld computers with paper forms for data collection in a national practice-based research network. They fi nd interesting tradeoffs between the 2 data collection methods.…”
Section: Revealing Methodsmentioning
confidence: 99%
“…[3][4][5] Four studies in this issue are from outside the United States, 1,3,4,5 and 1 shows the negative effects of acculturation to the United States. 6 This issue also features 2 studies of innovative primary care research methods, 7,8 and several other studies instruct us in novel methods by applying them to interesting questions. [1][2][3][4]9 The US Preventive Services Task Force provides us with 2 updates, 10,11 and a clinical trial tests a simple intervention hypothesized to reduce infl ammatory markers.…”
mentioning
confidence: 99%
“…8 Another US study on an anaesthetic service showed that a PDA was more effi cient, in terms of time taken and data completeness, in collecting data, than pen and paper. 9 Studies undertaken in developing countries showed similar results.…”
Section: Data Collection Process At Community Health Centresmentioning
confidence: 99%
“…Computerised medical record systems are less likely to result in missing clinical data than paper-based systems 248 which has been associated with fewer adverse events in Australian general practice. 249 Fewer missing data are also likely to improve the quality of research information derived from clinic data.…”
Section: Moving To Computerised Health Assessmentsmentioning
confidence: 99%
“…48,49 In addition to other benefits of computerised HAs described in Chapter 5, research data collected using computerised forms may be less likely to result in item non-response compared with paper-based forms. 248 …”
Section: Paper-based Health Assessmentsmentioning
confidence: 99%